A Systematic Review and Meta-Analysis of 19 Randomized Controlled Trials of Iguratimod Combined With Other Therapies for Sjogren’s Syndrome - Zeng, Liuting; He, Qi; Yang, Kailin; Hao, Wensa; Yu, Ganpeng; Chen, Hua (Frontiers in Immunology, 2022)
Objective: To explore the efficacy and safety of Iguratimod intervention in Primary Sjogren’s syndrome (pSS). Methods: Many databases were searched to collect the RCTs. Three independent reviewers extracted data and assessed the quality of the studies based on the Cochrane Handbook. The statistical analysis was done by RevMan 5.3 and STATA. The quality of evidence was evaluated by GRADE tool. This systematic review was registered in PROSPERO (CRD42020220770). Results: Twenty-nine RCTs with 2258 participants were included in this review. The meta-analysis shows that: iguratimod experiment group can reduce the ESSPRI score (WMD -1.93 [-2.33, -1.52], P<0.00001), ESSDAI score (WMD -1.39 [-1.81, -0.98], P<0.00001), Schirmer’s test (WMD 1.77 [0.85, 2.70], P=0.0002), RF (WMD -5.78 [-7.59, -3.97], P<0.00001), and decrease the ESR level (WMD -7.05 [-9.84, -4.26], P<0.00001). Meanwhile, the summary result showed the addiction of Iguratimod may not increase the adverse events. The adverse events were mainly gastrointestinal discomfort, abnormal liver function, and rash and itching. The quality of evidence of adverse events was moderate. Referring to minimal clinically important difference (MCID), the improvement of ESSPRI is clinically significant, and the improvement of ESSDAI for patients older than 60 years old may be clinically significant. Conclusion: Based on current evidence, iguratimod can effectively reduce ESSPRI score, ESSDAI score, Schirmer's test score and decrease systemic inflammatory response (such as ESR level and RF level) without increasing the probability of adverse events. The recommended course of treatment is at least 12 weeks.